(untitled) (The Peerian Journal, 2023)
Analysis of medicinal plant raw materials, as well as medicinal the forms and preparations obtained from it have their own characteristics and some difficulties, since cut, pressed, crushed and powdered objects are subject to research, and extracts are a complex of active and related substances that often interfere with the identification and analysis of each other